ANALISIS PENGGUNAAN FASILITAS TARIK TUNAI SALDO GOPAY MELALUI ATM XXX DENGAN MEKANISME TARIK TUNAI TANPA KARTU DI JAKARTA - Even Sitompul; Sugeng Santoso (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2021)
The bank is a financial service provider whose primary choice is for the community's financial-related needs. However, with increased mobility and the people's need for ease financial transactions, various technology-based innovations have emerged to safely, comfortably, and quickly fulfill community activities. One of the methods of financial service that has become the choice of Indonesians is finance technology (fintech). Fintech is a merger of the financial system various aspects of financial services. Go-Pay is a fintech in Indonesia that is a mobile payment service on the Go-Jek platform. Go-Pay provides to provide convenience and comfort for the transaction process carried out in Go-Jek. For banks not to be less competitive with Fintech, there is a need for adjustments and cooperation to strengthen business potential. PT. XXX (XXX) collaborates with Go-Pay in the Go-Pay cash withdrawal mechanism through XXX ATMs with the Cardless Cash Withdrawal mechanism as a form of banking synergy with fintech to facilitate transactions for Indonesians. This study purposes to determining how much the level of use of these facilities, especially in the community in Jakarta